Role playing game na educação: um estudo etnográfico - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The study seeks to analyze curricular skills raised by watched students while they were participants of a Rolling Playing Game (RPG) group with six children in Elementary School II from a Municipal School in the city of Fortaleza participated in the research. The group was watched during four months, every week. We used the ethnographic method. The ethnographic analysis points to the fact that RPG can raise student’s habilities from the Portuguese language curricular component, English language curricular component and, mainly, Arts curricular component, moreover it is possible to envole the digital media in the process. All this done in a ludic and enjoyable way for the students. At the same time, some mishaps were noted that may take on a larger scale in a real classroom context.
Keywords: Jogos de fantasia; Ensino - Meios auxiliares; Role Playing Game (RPG); Habilidades pessoais; Fantasy games; Teaching - Auxiliary means; CNPQ::CIENCIAS SOCIAIS APLICADAS